He Matatauihi i Ngā Ururei Whēako hei Kahu Pōkai: The Experiences of Being a Māori Midwife - Leatham, Beatrice-Ann Materoa (Auckland University of Technology, 2025)
This thesis explores the intricate nature of Indigenous midwifery within Aotearoa. The context has largely been constructed through the ethnocentric worldview of non-Māori and there is very little written that explores the understandings of being a Māori midwife or Kahu Pōkai. This realisation presented a sense of urgency to document distinctively Māori maternity knowledge. Repetitive evidence shows many Indigenous whānau are unable to access care that positively enhances their childbirth experience, and endure inequitable maternity outcomes and culturally unsafe experiences. By giving Māori midwives the opportunity to tell their stories this research aimed to reveal the uniqueness of Māori midwifery practice. In doing this, Indigenous midwifery knowledge that may provide alternative understandings to better support birthing whānau is exposed. ‘He Matatauihi i ngā Ururei Whēako hei Kahu Pōkai’ embodies the focus of this study. ‘Matatauihi’ refers to the sacred role of calling spiritual and physical energies to kaupapa (topic, focus) by the female voice. ‘Ngā Ururei’ conveys the ancient practices that are guided by the knowledge of deities. ‘Wheako’ are the experiences gained by the being that is human; and ‘Kahu Pōkai’ refers to the absolute commitment, unique passion and purpose that is activated for mothers and their babies. This title locates the study to the nature of Māori midwifery and childbirth. It exerts knowledge systems of both the tangible and intangible, acknowledges the responsibility of nurturing whakapapa, and offers insight to the privileged potential of this position. Nine Māori midwives told their stories. Their insights are documented, building upon a limited source of literature on Māori midwifery in Aotearoa. Kaupapa Māori and Mana Wahine were crucial theoretical frameworks that allowed distinct Indigenous systems of knowledge to be integrated into the research. Hence, a traditional Māori pedagogy of learning was implemented. Te Whare-kōrero ā Kahu Pōkai provided the philosophical underpinning to ground the research in mātauranga Māori, specific to Kahu Pōkai. Preferencing knowledge in this way revealed Māori midwives practice in a transformative manner. They innately resist the patriarchal systems in which Māori maternities currently dwell to assert tino rangatiratanga (self-determination) of themselves and birthing whānau. Kahu Pōkai displayed an astute ability to navigate two often opposing worldviews, achieving maternity care that is responsive to the needs of birthing whānau. This research makes several proposals; first and foremost, the need for Kahu Pōkai education that is firmly positioned in Māori pedagogy has become evident. Enduring negative Māori maternity outcomes demonstrate the Aotearoa midwifery sector is not cognisant to the significance of historical, cultural, and political prejudice. Robust understanding of this environment is crucial to the current context of midwifery. Significantly, there is a growing appetite for health services that are underpinned by mātauranga Māori. In response, a review of current midwifery practice models, especially the primary elements of the Partnership model, is critical. Further, supporting Kahu Pōkai to advance their cultural aspirations will strengthen the cultural capacity, retention, and, therefore, sustainability of the workforce. This will be crucial as Māori birthing rates increase.